Phương pháp tổng quát tính trao đổi nhiệt bức xạ giữa hai mật bất kỳ - Nguyễn, Bốn (Bộ Giáo dục và Đào tạo, 2013)
This article introduces a new simple method to determine the radiation exchange heat of two anysurfaces by determining its' equivalent radiation coefficient. The introduced formules may be use in radiation heat calculating of heat exchange equipments with technology accuracy .